Anticipating Greater Impact of the COVID-19 Pandemic on Social Life Is Associated With Reduced Adherence to Disease-Mitigating Guidelines - Plate, Rista C.; Jenkins, Adrianna C. (Frontiers in Psychology, 2022)
People regularly make decisions about how often and with whom to interact. During an epidemic of communicable disease, these decisions gain new weight, as individual choices exert more direct influence on collective health and wellbeing. While much attention has been paid to how people’s concerns about the health impact of the COVID-19 pandemic affect their engagement in behaviors that could curb (or accelerate) the spread of the disease, less is understood about how people’s concerns about the pandemic’s impact on their social lives affect these outcomes. Across three studies (total N = 654), we find that individuals’ estimates of the pandemic’s social (vs. health) impact are associated with an unwillingness to curtail social interaction and follow other Centers for Disease Control guidelines as the pandemic spreads. First, these associations are present in self-report data of participants’ own behaviors and behavior across hypothetical scenarios; second, participants’ estimates of the pandemic’s impact on social life in their U.S. state of residence are associated with movement data collected unobtrusively from mobile phones in those locations. We suggest that perceptions of social impact could be a potential mechanism underlying, and therefore potential intervention target for addressing, disease-preventing behavior during a pandemic.